A survey of characteristics and current educational needs of hemophilia treatment centers within Asia Pacific. Issue 3 (24th May 2018) - Lam, Joyce C. M.; John, M. Joseph; Street, Alison; ,
Abstract: Background: Poor disease understanding and gaps in expertise regarding hemophilia care have been identified at all levels in Asia Pacific. Continued education for involved healthcare professionals (HCPs) is crucial for improved delivery. Objectives: To identify training and educational needs of hemophilia HCPs in Asia Pacific. Methods: Clinicians working at hemophilia treatment centers (HTCs), identified from the World Federation of Hemophilia Directory, were contacted by the Asia Pacific Hemophilia Working Group (APHWG). An electronic survey was sent to 161 centers from 15 countries for which HTC identification was complete to assess HTC characteristics, educational status, and needs. Responses were stratified by national economic capacity. Results: From March 23 to June 6, 2016, clinicians from 58 HTCs completed the survey. Most reported availability of specialists to serve core patient requirements, although availability of trained nurses and geneticists was low in lower‐middle income countries (LMICs). Although 98.3% of HTCs had laboratory facilities, 8.8% do not participate in any quality assessment schemes. The most common limitations of current initiatives were infrequency and lack of local language content. Education is currently mostly received via internet, particularly among LMICs and upper‐middle income countries (UMICs), though there is strong preference for meetings. Main barriers to receiving education were funding and time constraints. Unique priority topics were musculoskeletal management, quality of life and management by non‐hematologists (high‐income countries), inhibitor management and research (UMICs), and outcomes assessment (LMICs). Conclusion: In Asia Pacific, training programs should be tailored according to unique needs of differing economic capacities and resource settings.